When Clinicians Are Summoned to Testify in Court: Orientation to the Process and Suggestions on Preparation - Janet L. Murphy MSN, RN, APRN, CPNP, SANE-P (SAGE Publishing, 2018)
There are occasions when clinicians are summoned to court to testify. The reasons for this are wide-ranging. It can be about the provision of patient care that is relevant to a criminal or civil legal matter, or to a malpractice complaint, concerns of safety for a child, child custody issue, allegation of sexual or physical abuse, or being called to testify as an expert witness in your field of expertise. The legal system is adversarial and litigation is the process used to determine the considered truth of the matter at hand. The adversarial nature of the courtroom stands in stark contrast to the collaborative mindset and approach used in health care. Most clinicians will never have to testify in a court setting. However, when a clinician does receive a subpoena, feelings of dread, anxiety, and panic can ensue. This can be especially harrowing if the subpoena is about a malpractice grievance. Understanding the legal arena, court proceedings and how to properly prepare, can assist the clinician to navigate the process and stay calm under pressure if subpoenaed to testify. This article will help clinicians know what to do and how to prepare in the event they are ordered to testify in court. An orientation to the courtroom, basic legal concepts, and definitions will be discussed. This article is structured in a question and answer format based on typical questions clinicians ask when anticipating going to court.